Penerapan Standar Nasional Pemeriksaan Odontologi Di Rumah Sakit Bhayangkara Nusa Tenggara Barat Tahun 2022 - Hadyljinan Utomo, Danesh; Arnawati, Ida Ayu; Syamsun, Arfi (Yayasan Jompa Research and Development, 2025)
Odontological examination is a primary identification method that is especially crucial in cases involving severely damaged, decomposed, or burned bodies where other identification techniques such as fingerprints or DNA are not applicable. Therefore, the inclusion of complete and accurate dental examination findings in the Visum et Repertum is essential to ensure the validity of victim identification and to strengthen the evidentiary value in legal proceedings. This study aims to determine the extent of the implementation of national standards in forensic odontology examinations at the Bhayangkara Hospital, NTB during 2022. The method used is descriptive observational with a cross-sectional approach, using secondary data from Visum et Repertum (VeR) letters. The results showed that out of 13 cases, only five cases (38.5%) met the national standards completely, while the rest were incomplete or there was no recording at all. In conclusion, there is still a discrepancy between the implementation and recording of odontology examinations with applicable standards.